Lake Wingra: Changing Perceptions and Land-Use Decisions of Madison Wetlands - Elmer, Holly; Bodden, Matthew; Perry, Rebecca; McLester, Caitlin (My University, 2011)
Madison, Wisconsin is characterized by the presence of the University of Wisconsin and the Wisconsin State Capitol. Surrounded by a beautiful chain of fresh water lakes, the scenic nature of Madison's surroundings have always played an important part in the policy decisions that have formed the city. This paper uses the historical discourses centering around our study area of Lake Wingra, on the East side of Madison, as examples of the dynamics surrounding landscape-forming decisions. Analysis of wetlands extent over time confirms that the majority of wetland reclamation in the study are occurred before 1959. A detailed analysis of discourses about wetlands suggests that wetlands were regarded as useless and ugly, contributing to local dispositions in favor of dredging and filling. Most filling took place before accurate scientific understanding of the value of wetland-provided ecosystem services could inform policy decisions. Most land reclamation in the state occurred for agricultural purposes, but wetland filling in Madison was carried out for institutional purposes. A comparison between institutionally-owned land and privately-owned land suggests that institutional use such as parks are less damaging to the health of fresh water lakes than private free-market use.
Includes Figures, Illustrations, Images, Maps and Bibliography.
Keywords: Land use; Madison, WI; Wetlands; Lake Wingra